Peningkatan Kapasitas dan Kualitas Pengelolaan Arsip dan Kearsipan - Yusuf, M; Masduki, Masduki; Kholik, Abdul (LP3M STAI Darussalam Krempyang Nganjuk, 2020)
The Mentoring of Office administrative Governance in the form of archives and archival in Madin Hidayatul Mubtadiin Gebangkerep Baron Nganjuk was conducted through training and mentoring that could be a catalyst to increase the effectiveness and efficiency of administrative governance for human resources or managers of Madrasah Diniyah. This Program aims to improve how the management of administrative activities in the form of archives and archival in Madin Hidayatul Mubtadiin can run as standard of education administration. With this mentoring is expected to help the progress of the management of the percussion that will also impact the improvement of the quality of religious education in the side of its managerial, human resources, and administrative activities.